Time and scale in Life Cycle Assessment: the case of fuel choice in the transport sector. (22nd July 2008) - Hillman, Karl M.; Sanden, Bjorn A.
Life Cycle Assessments (LCA, including Well-to-Wheel studies) that are to support decisions that strive to change large technical systems need to consider time and scale related factors, which are given little attention in standard LCA procedures. Here, we address three issues and provide examples from the case of alternative fuels. First, shifting time frame gives room for technical development that should affect not only the choice of performance data, but perhaps also the functional unit and the selection of technologies under study. Secondly, background systems, such as heat and power production, change over time and increased production volumes of the alternative fuel change the transport system that is used to produce transport fuel. We show that such changes have consequences not only for Greenhouse Gas (GHG) emissions from each fuel-chain, but also for the ranking order of, e.g. Rapeseed Methyl Esther (RME) and ethanol in terms of GHG emissions. Finally, different types of feedstock are available in different quantities and different by-product markets vary in size. Key markets for RME by-products in EU correspond to an RME production that covers about 3% of transport fuel demand. Consequently, GHG emissions that are allocated to the fuel should change with the scale of adoption.